Parametric Optimization of Technological Processes - Urinov Nasillo Fayzilloevich; Dubrovets Lyudmila Vladimirovna; Shukurova Madina Shavkat qizi (Genius Journals, 2022)
The article presents the definition of parameters of cutting conditions that optimize the main indicators of production efficiency, such as productivity, cost.
Keywords: Tool life; roughness; machined surface; product quality